Investigating User's Attentional Focus in Computational Environments: A Literature Review with Emphasis on Webcam Data - Souza, Cassiano da Silva; Silveira, Milene Selbach; Manssour, Isabel Harb (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2024)
Maintaining the user’s attentional focus has become a recurring concern in recent years. This is due to the consolidation of remote and hybrid models for study and work, which were widely experienced during the social distancing caused by COVID-19. This paper presents a review of works that address this problem by analyzing webcam data, a promising device for behavioral studies. The literature review from 2013 to 2023 was carried out using a hybrid search strategy, through which we selected and analyzed 57 papers. The summary of this study is presented in an interactive visual survey format called the AttentionVis Browser tool. As additional contributions, we provide a list of lessons learned, a list of work limitations, and possibilities for future research.